HUBUNGAN ANTARA KELOMPOK TEMAN SEBAYA DENGAN PERILAKU SEKSUAL PRANIKAH PADA REMAJA DI KELURAHAN X PALEMBANG - Oktaviana, Rina (Jurnal Ilmiah Psyche, 2015)
This study aimed to explore  the relationship between peer group with premarital sexual behavior among adolescents in Kelurahan "X" Palembang. The independent variable in this study is the peer group. Meanwhile, the dependent variableis the premarital sexual behavior. The hypothesis proposed in this study, there?s relationship between peer group with premarital sexual behavior among adolescents in Kelurahan "X" Palembang. Sampling studies using proportionate random sampling technique. The data in this study were drawn using a scale of peer groups and premarital sexual behavior scale. Analysis of research data is implemented using a simple regression analysis techniques (simpele regression). All calculations done using SPSS version 19.00. The results showed that there was a very significant relationship between peer group with premarital sexual behavior among adolescents in  Kelurahan "X" Palembang (r=0.558, p =0.000orp<0.01). Furthermore, an effective amount of donations given to the peer group variable premarital sexual behavior amounted to 31.1%.